2014
DOI: 10.1111/nuf.12105
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Patients in Their Care Versus Obscurantism

Abstract: As scientists and healthcare providers, we have the duty to counter obscurantism by promoting understanding of the health of individual citizens and society at large. A culture change in healthcare systems toward being patient-centric and placing value on patient engagement is warranted, and this change must come from healthcare providers. Patient-centered tools that support patient engagement, patient portals, or personal health records are still needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…The committee issued ten recommendations to improve safe use of health IT, and concluded that health IT is expected to make health care more efficient and safe. Tzeng, Yin, & Fitzgerald (2015) assert health care providers must value this new culture of patient involvement, including supporting tools such as patient portals which allow patient and health care provider collaboration. As the largest segment of health care providers, nurses may be best positioned to lead adoption of EHR to promote better patient care, as stated in a 2010 report, "The Future of Nursing: Leading Change, Advancing Health" from the IOM.…”
Section: Background/statement Of the Problemmentioning
confidence: 99%
“…The committee issued ten recommendations to improve safe use of health IT, and concluded that health IT is expected to make health care more efficient and safe. Tzeng, Yin, & Fitzgerald (2015) assert health care providers must value this new culture of patient involvement, including supporting tools such as patient portals which allow patient and health care provider collaboration. As the largest segment of health care providers, nurses may be best positioned to lead adoption of EHR to promote better patient care, as stated in a 2010 report, "The Future of Nursing: Leading Change, Advancing Health" from the IOM.…”
Section: Background/statement Of the Problemmentioning
confidence: 99%
“…Since a health co-op's mission is to empower members-patients (Girard, 2014;Novkovic, 2008) and an ePHR's purpose is similarly to empower patients (Tzeng et al, 2015), we suggest that there is a natural internal social alignment between a health co-op and an ePHR.…”
Section: Intra-organizational Social Alignmentmentioning
confidence: 99%
“…Empowering the patient is an integral part of the ePHR tool, since it allows individuals to control their personal information and, thus, to place themselves in the forefront of the management of their own health records (Tzeng et al, 2015). Similarly, health co-ops contribute to empowering their patients and members through their democratic functioning (Girard, 2014;Novkovic, 2008).…”
Section: Intra-organizational Social Alignmentmentioning
confidence: 99%
See 2 more Smart Citations